Low threshold tunable spaser based on multipolar Fano resonances in disk–ring plasmonic nanostructures. (25th November 2015) - Zheng, Chunjie; Jia, Tianqing; Zhao, Hua; Zhang, Shian; Feng, Donghai; Sun, Zhenrong
Abstract: In this paper, we study theoretically spasers based on multipolar Fano resonances in disk-ring nanostructures covered with a silica layer doped with Yb 3+ :Er 3+ used as the gain material. The electric field amplitudes at the quadrupolar mode (lasing wavelength) and the octupolar mode (pumping wavelength) are simultaneously enhanced by tens of times. Moreover, the spaser operates in a dark mode, which can reduce the radiation loss and enhance the confinement effectively. These factors work together to decrease greatly the critical gain coefficient and threshold. By adjusting the elliptic partial degrees of the nano-ring, the spasers can be tuned in the range of 1550 to 1650 nm, while the pumping light remains at the 980 nm absorption band of Yb 3+ ions. Moreover, the spasers at three Fano resonance wavelengths of the disk-ring nanostructures appear in sequence with increasing the gain coefficient. The effects of the extinction coefficient on the electric field amplitudes of the pump light are also studied.